Combining Cellulose and Cyclodextrins: Fascinating Designs for Materials and Pharmaceutics - Cova, Tânia F.; Murtinho, Dina; Pais, Alberto A. C. C.; Valente, Artur J. M. (Frontiers in Chemistry, 2018)
Cellulose and cyclodextrins possess unique properties that can be tailored, combined and used in a considerable number of applications, including textiles, coatings, sensors and drug delivery systems. Successfully structuring and applying cellulose and cyclodextrins conjugates requires a deep understanding of the relation between structural, and soft matter behavior, materials, energy, and function. This review focuses on the key advances in developing materials based on these conjugates. Relevant aspects regarding structural variations, methods of synthesis, processing and functionalization, and corresponding supramolecular properties are presented. The use of cellulose/cyclodextrin conjugates as intelligent platforms for applications in materials science and pharmaceutical technology is also outlined, focusing on drug delivery, textiles and sensors.